Toratau Geopark As a Catalyst for Sustainable Development and Ecological Tourism in The Republic of Bashkortostan - Ilgizovna, Shafeeva Elina; Rinatovich, Miftakhov Ilnur (Journal of Ecohumanism, 2024)
The article is dedicated to the analysis of the problems and prospects for the development of the Toratau Geopark as a key element of sustainable tourism and natural heritage conservation in the Republic of Bashkortostan. The study identified major management limitations of the geopark, such as insufficient marketing activity, seasonal fluctuations in tourist flows (with the summer season accounting for about 80% of total visits), limited financial resources (with approximately 16 million rubles invested in infrastructure), the need to enhance visitors’ ecological awareness, and challenges in coordination with local organizations. Educational events are planned to manage the impact on natural sites and improve ecological awareness, as over 64.7% of visitors are interested in eco-tourism. The proposed solutions aim to improve coordination with local organizations, attract investors, and develop infrastructure. The results highlight the importance of a comprehensive approach to management, which will increase the geopark’s attractiveness and ensure its sustainable development, including the preservation of natural heritage for future generations.